2022
DOI: 10.48550/arxiv.2201.10766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Study of Image Classification Model Sensitivity to Foregrounds, Backgrounds, and Visual Attributes

Abstract: While datasets with single-label supervision have propelled rapid advances in image classification, additional annotations are necessary in order to quantitatively assess how models make predictions. To this end, for a subset of ImageNet samples, we collect segmentation masks for the entire object and 18 informative attributes. We call this dataset RIVAL10 (RIch Visual Attributes with Localization), consisting of roughly 26k instances over 10 classes. Using RIVAL10, we evaluate the sensitivity of a broad set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Spurious correlations in natural image datasets. Multiple works demonstrated that natural image datasets contain spurious correlations that hurt neural network models [50,100,89,3,90,91,64]. Notably, Geirhos et al [27] demonstrated that ImageNet-trained CNNs are biased towards texture rather than shape of the objects.…”
Section: Related Workmentioning
confidence: 99%
“…Spurious correlations in natural image datasets. Multiple works demonstrated that natural image datasets contain spurious correlations that hurt neural network models [50,100,89,3,90,91,64]. Notably, Geirhos et al [27] demonstrated that ImageNet-trained CNNs are biased towards texture rather than shape of the objects.…”
Section: Related Workmentioning
confidence: 99%